Design, Implementation & Performance Analysis of Solar Tracking System on Simulink Platform. Issue 1 (December 2020) - Mamodiya, Udit; Tiwari, Neeraj
Abstract: This paper presents the idea of tracking framework which was executed on Simulink stage. The variety in current and voltage for static and tracking SPV power plant are appeared in this paper. The relative study at various situating of panel (static force plant) is additionally appeared in this paper. The entire model like sun tracking model, static SPV model, LDR sensor model, DC motor model additionally appeared in the paper. The primary goal of this paper is to break down the outcomes concerning static force plant. The tiltaion edges are 30°, 60° and 90° static force plants. The simulation results and the impact of tiltation point are additionally introduced in this paper. In the closing comment, the improved effectiveness because of tracking method is appeared.